A LEGAL PERSPECTIVE ON COMBATING CUSTODIAL RAPE AND ENSURING JUSTICE IN INDIA - Mridula Devi; Firdosa, Taslima (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The bureau of police plays a very significant role in the criminal justice system. In India the performance of police agency has been very dynamic, not only their duty is to collect evidence but also to facilitate protection to the victims as well as the society as a whole. However there are several occurrences in the past decade where instead of providing protection to the society, some of the officers of the police fraternity had committed some heinous crime with the people under their custody. The offence of rape is one of such crimes in that category. There are several precedents wherein the Honorable Supreme Court of India as well as the Honorable High Courts of India has pronounced some stringent punishments in such cases of custodial rape. Several pronouncements have led to amendments in the core legislations of India. From time to time the law commission of India has put forward certain recommendations to the legislature of India. Accordingly the legislature of India has enacted Criminal Law Amendment Act in the year 2013 and 2018. It has made certain amendments in the Indian Penal Code 1860, Criminal Procedure Code 1973, and Evidence Act 1872 and in the Protection of Children from Sexual Offences Act 2012. The new amendments have incorporated changes in the earlier laws as well as have inserted new provisions in the earlier legislations. Now the law has become more particular and deterrent in context of custodial rape. The punishments have been increased including imprisonment for the remainder of life and fine. The new provisions also provide compensations to the victims of rape. This research paper focuses on the legal developments made in the legislations of India curbing and preventing the custodial rape practice in India.